A contribution to the knowledge of the Embolemidae of Gabon, Costa Rica and Papua New Guinea (Hymenoptera Chrysidoidea) (Bollettino di zoologia agraria e bachicoltura, 2024)
Three new species of Embolemidae are described: Embolemus gabonensis (from Gabon), E. hansoni (from Costa Rica) and E. searsi (from Papua New Guinea). The male of Ampulicomorpha gressitti Olmi is described for the first time. New keys to the Embolemidae are proposed.
Keywords: Embolemidae; Embolemus gabonensis; Embolemus hansoni; Embolemus searsi; Ampulicomorpha gressitti; Gabon; Costa Rica; Papua New Guinea